A Synthetic Single-Site Fe Nitrogenase: High Turnover, Freeze-Quench (57)Fe Mössbauer Data, and a Hydride Resting State - Del Castillo, Trevor J; Thompson, Niklas B; Peters, Jonas C (Journal of the American Chemical Society, 2016)
The mechanisms of the few known molecular nitrogen-fixing systems, including nitrogenase enzymes, are of much interest but are not fully understood. We recently reported that Fe-N2 complexes of tetradentate P3(E) ligands (E = B, C) generate catalytic yields of NH3 under an atmosphere of N2 with acid and reductant at low temperatures. Here we show that these Fe catalysts are unexpectedly robust and retain activity after multiple reloadings. Nearly an order of magnitude improvement in yield of NH3 for each Fe catalyst has been realized (up to 64 equiv of NH3 produced per Fe for P3(B) and up to 47 equiv for P3(C)) by increasing acid/reductant loading with highly purified acid. Cyclic voltammetry shows the apparent onset of catalysis at the P3(B)Fe-N2/P3(B)Fe-N2(-) couple and controlled-potential electrolysis of P3(B)Fe(+) at -45 °C demonstrates that electrolytic N2 reduction to NH3 is feasible. Kinetic studies reveal first-order rate dependence on Fe catalyst concentration (P3(B)), consistent with a single-site catalyst model. An isostructural system (P3(Si)) is shown to be appreciably more selective for hydrogen evolution. In situ freeze-quench Mössbauer spectroscopy during turnover reveals an iron-borohydrido-hydride complex as a likely resting state of the P3(B)Fe catalyst system. We postulate that hydrogen-evolving reaction activity may prevent iron hydride formation from poisoning the P3(B)Fe system. This idea may be important to consider in the design of synthetic nitrogenases and may also have broader significance given that intermediate metal hydrides and hydrogen evolution may play a key role in biological nitrogen fixation.